Analisis Wacana Multimodal pada Platfrom Pembelajaran Bahasa Indonesia: Studi Kasus Penggunaan SIPEBI - Pratiwi, Aura Ayudya; Sugiarlyna, Bunga Jeassica; Yanni, Desvita Risma; Toban, Gracelia; anhar, Anhar (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze multimodal discourse construction in digital-based Indonesian language learning materials with a case study on the SIPEBI platform. The approach used is descriptive-analytical qualitative with a Systemic Functional Multimodal Discourse Analysis (SF-MDA) theoretical framework to examine the relationship between modalities in constructing pedagogical meaning. The research object includes multimodal discourse in digital materials, which is examined through a comprehensive literature study of journals and academic books focusing on multimodal discourse analysis, multimodality theory, and technology-based language learning. The results show that SIPEBI is capable of integrating various modes, such as text, images, audio, video, and interactive elements that support each other in constructing learning meaning. The interaction between these modes produces three main functions, namely reinforcement, complementarity, and integration, which contribute to improving understanding, engagement, and adaptation to students' diverse learning styles. Thus, Indonesian language learning through SIPEBI becomes more contextual and meaningful.